Streptococcus pneumoniae: a Plethora of Temperate Bacteriophages With a Role in Host Genome Rearrangement - Martín-Galiano, Antonio J.; García, Ernesto (Frontiers in Cellular and Infection Microbiology, 2021)
Bacteriophages (phages) are viruses that infect bacteria. They are the most abundant biological entity on Earth (current estimates suggest there to be perhaps 1031 particles) and are found nearly everywhere. Temperate phages can integrate into the chromosome of their host, and prophages have been found in abundance in sequenced bacterial genomes. Prophages may modulate the virulence of their host in different ways, e.g., by the secretion of phage-encoded toxins or by mediating bacterial infectivity. Some 70% of Streptococcus pneumoniae (the pneumococcus)—a frequent cause of otitis media, pneumonia, bacteremia and meningitis—isolates harbor one or more prophages. In the present study, over 4000 S. pneumoniae genomes were examined for the presence of prophages, and nearly 90% were found to contain at least one prophage, either defective (47%) or present in full (43%). More than 7000 complete putative integrases, either of the tyrosine (6243) or serine (957) families, and 1210 full-sized endolysins (among them 1180 enzymes corresponding to 318 amino acid-long N-acetylmuramoyl-L-alanine amidases [LytAPPH]) were found. Based on their integration site, 26 different pneumococcal prophage groups were documented. Prophages coding for tRNAs, putative virulence factors and different methyltransferases were also detected. The members of one group of diverse prophages (PPH090) were found to integrate into the 3’ end of the host lytASpn gene encoding the major S. pneumoniae autolysin without disrupting it. The great similarity of the lytASpnand lytAPPH genes (85–92% identity) allowed them to recombine, via an apparent integrase-independent mechanism, to produce different DNA rearrangements within the pneumococcal chromosome. This study provides a complete dataset that can be used to further analyze pneumococcal prophages, their evolutionary relationships, and their role in the pathogenesis of pneumococcal disease.